Identification of a novel cord blood NK cell subpopulation expressing functional programmed death receptor-1 - Greppi, Marco; Obino, Valentina; Goda, Rayan; Rebaudi, Federico; Carlomagno, Simona; Della Chiesa, Mariella; Sivori, Simona; Ubezio, Gianluca; Agostini, Vanessa; Bo, Alessandra; Pesce, Silvia; Marcenaro, Emanuela (Frontiers in Immunology, 2023)
Background Natural Killer cells (NKs) represent the innate counterpart of TCRαβ lymphocytes and are characterized by a high anti-tumor and an anti-viral cytotoxic activity. Recently, it has been demonstrated that NKs can express PD-1 as an additional inhibitory receptor. Specifically, PD-1 was identified on a subpopulation of terminally differentiated NKs from healthy adults with previous HCMV infection. So far it is unknown whether PD-1 appears during NK-cell development and whether this process is directly or indirectly related to HCMV infection. Methods In this study, we analyzed the expression and function of PD-1 on Cord Blood derived NKs (CB-NKs) on a large cohort of newborns through multiparametric cytofluorimetric analysis. Results We identified PD-1 on CB-NKs in more than of half the newborns analyzed. PD-1 was present on CD56dim NKs, and particularly abundant on CD56neg NKs, but only rarely present on CD56bright NKs. Importantly, unlike in adult healthy donors, in CB-NKs PD-1 is co-expressed not only with KIR, but also with NKG2A. PD-1 expression was independent of HCMV mother seropositivity and occurs in the absence of HCMV infection/reactivation during pregnancy. Notably, PD-1 expressed on CB-NKs was functional and mediated negative signals when triggered. Conclusion To our understanding, this study is the first to report PD-1 expression on CB derived NKs and its features in perinatal conditions. These data may prove important in selecting the most suitable CB derived NK cell population for the development of different immunotherapeutic treatments.